Directions in Australian electoral reform : professionalism and partisanship in electoral management - Kelly, Norm (ANU E Press, 2012)
Assesses Australian electoral reforms of the past 30 years using personal interview data and parliamentary debates, to provide a picture of the reform process as well as the outcomes.